Gut microbiota dysbiosis in inflammatory bowel disease: interaction with intestinal barriers and microbiota-targeted treatment options - Hongjun Xie; Hongjun Xie; Siyan Yu; Siyan Yu; Mingyu Tang; Mingyu Tang; Yating Xun; Yating Xun; Qin Shen; Qin Shen; Gaojue Wu; Gaojue Wu; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
Recent studies have deepened our understanding on gut microbiota alterations and the interaction with intestinal barrier impairments, which play a crucial role in the etiology and pathophysiology of Inflammatory bowel disease (IBD). The intestinal microbiota dysbiosis in IBD including the altered microbiota composition, decreased beneficial species and increased harmful species. The disturbed gut microbiota results in the aggravation of intestinal barrier dysfunction through regulation of antimicrobial substances in mucus layer, tight junction protein in mechanical layer and inflammatory response in immune layer. The therapeutic options targeted on the microbiota including antibiotics, probiotics and fecal microbiota transplantation (FMT) exhibit efficacies and limitations in the treatment of IBD. Reasonable single or combined use of these treatments can restore intestinal microecological homeostasis, which further contributes to the treatment of IBD. This review analyzes the underlying mechanisms for the interaction between microbiota alterations and gut barrier dysfunction in IBD; meanwhile, it provides new insights into the microbiota-targeted therapeutic options IBD, including the benefits, risks and limitations of antibiotic and probiotic therapies, unresolved clinical application strategies for FMT, and combination administrations of antibiotics and FMT.